1989
DOI: 10.1073/pnas.86.24.9662
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of amylin, a peptide associated with type 2 diabetes mellitus.

Abstract: The 37-amino acid peptide called amylin is a major component of the islet amyloid deposited in the pancreases of persons with type 2 diabetes mellitus. We report the isolation of a partial cDNA clone and a phage A genomic clone of the coding region of the amylin gene. The DNA sequence encodes a protein sequence identical to that of amylin isolated from the amyloid found in the diabetic pancreas and shows that amylin is likely to be synthesized as a precursor peptide, now named proamylin. We have demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 40 publications
2
83
1
Order By: Relevance
“…1), which is reminiscent of vertebrate CGRP, adrenomedullin, and amylin ( Fig. 1B) (3,(25)(26)(27). In addition, the peptides contained a C-terminal Pro-NH 2 , which is characteristic of vertebrate CT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1), which is reminiscent of vertebrate CGRP, adrenomedullin, and amylin ( Fig. 1B) (3,(25)(26)(27). In addition, the peptides contained a C-terminal Pro-NH 2 , which is characteristic of vertebrate CT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1D) between hA and mA in the segment corresponding to NNFGAILSS (dashed line) in large part generate the amyloidogenic nucleus in hA that is largely responsible for its propensity to misfold, aggregate, elicit death by apoptosis of islet Ī²-cells, and cause islet degeneration and diabetes [13]. The intramolecular disulphide bond and carboxyl-terminal amide group are required for physiological hormonal activity of hA [6,14].…”
Section: Resultsmentioning
confidence: 99%
“…However, it seems likely that an optimal spacer length between the peptide and the bulk of the attached derivative is required to fully prevent steric hindrance of receptor-ligand interactions. In this regard we have found that the N-terminal region of amylin and CGRP plays a role in receptor binding since reduction of the 2-7 disulphide bridge abolishes receptor recognition (C. Bacon and A. Chantry, unpublished observations) and biological activity [11]. The biotinylated analogues de-" scribed here have a spacer with a disulphide bridge and 8 atoms between the biotinyl carboxyl group and the N.terminal Lys.…”
Section: Discussionmentioning
confidence: 99%